Gender essentialism and occupational segregation in insolvency practice - Joyce, Yvonne; Walker, Stephen P. (Accounting, Organizations and Society, 2015)
Advances towards egalitarianism in professional recruitment may be offset by processes of occupational re-segregation. Drawing on gender theory this paper investigates horizontal segregation in the UK insolvency profession, as revealed through the lived experiences of female and male practitioners. It is shown that horizontal segregation pervades at different levels of practice and is undergirded by various elements of gender essentialism. Physical essentialism explains why insolvency practice has been traditionally gendered male. Interactional essentialism combines with the management of work-life balance to define the subfields of corporate and personal insolvency as masculine and feminine respectively. Gender essentialist assumptions also pervade the distribution of roles and the allocation of work tasks. Networks are identified as arenas for the reproduction and perpetuation of occupational segregation. The findings indicate the continuing potency of gender in everyday professional life, the limitations of diversity-orientated policies and the complexities of formulating transformative agendas.